Role of IL-17F in the Pathogenesis of Psoriasis - Nakajima, Masayuki; Kawaguchi, Mio; Watanabe, Hideaki; Morishima, Yuko; Huang, Shau-Ku; Satoh, Hiroaki; Hizawa, Nobuyuki (Current Immunology Reviews (Discontinued), 2016)
Psoriasis is a complex autoimmune inflammatory disease with a genetic basis. The increased expression of IL-17F gene and protein is observed in the lesional skins of psoriatic patients. We and other groups discovered human IL-17F gene that shows the highest homology with IL-17A. IL-17F induces various inflammatory molecules, such as IL-6 and IL-8. IL-17F is mainly derived from Th17, Tc17 and ILC3 cells, and induces CCL20 expression, resulting in the recruitment of additional IL-17F-producing cells to enhance skin inflammation via CCR6. The receptor for IL-17F is the heterodimeric complex of IL-17RA and IL-17RC, and several signaling pathways have been identified. Injection with IL-17F in mice revealed marked neutrophilia in dermis, and its infiltration was significantly inhibited by anti-IL-8 antibody. Sequence variants of the IL-17F gene are associated with response to treatments, and a variant (rs763780) of IL-17F encodes an antagonist for the wild-type IL-17F. Hence, IL-17F may play a pivotal role in the pathogenesis of psoriasis, and may provide a promising therapeutic target for development of novel strategies.
Keywords: Psoriasis